CRITICAL LITERACY IN JUNIOR HIGH SCHOOL - Astarina, Atri Nadia (2015)
This study incorporates critical literacy (CL) to the English teaching program to examine the enhancement of eighth grade junior high school students' critical literacy. This qualitative case study also investigates the benefits and challenges found during the English teaching program. The data were obtained from classroom observations, students' reflective learning journals, students' reading works, questionnaire, and interview. The obtained data were analyzed using theories of CL, including critical social theory of literacy (Wallace, 2003), critical pedagogy (Freire, 2005), the four dimensions model of critical literacy (Lewison,et.al, 2002) and the criteria of critical literacy (Sandretto, 2011). The study reveals that the incorporation of CL to the English teaching program has assisted students to be critically literate in three ways. Firstly, this incorporation encouraged students to be aware of text as value-laden. Secondly, it established a democratic atmosphere and non-threatening environment. Lastly, it positioned the teacher as an expert who is influential in facilitating and leading students' discussion and learning. The aforementioned features promoted benefits which involve students' CL development, students' English proficiency improvement, and a more active class dynamics. Nevertheless, these benefits might be constrained by time of learning, students' English proficiency, and teachers' competence. Thus, in order to have effective results, it is recommended that a CL is incorporated to the English teaching program with the consideration of selecting appropriate topics, materials, and media, as well as organizing well-managed teaching activities. Key words: Critical literacy, English teaching program